Enhancing environmental education through community service learning: a qualitative exploration of curriculum integration - Maribel B. Zamora (Science and Education, 2023)
This study explored the integration of environmental education into the curriculum through community service learning (CSL) in the Philippines. A review of related literature and DepEd orders related to environmental education curriculum integration was conducted to provide a comprehensive overview of the topic. The study found that there is a growing interest in integrating environmental education into the curriculum in the Philippines, and that community service learning is a promising approach for achieving this goal. However, the implementation of DepEd orders related to environmental education curriculum integration remains inconsistent and faces various challenges. The review highlighted the benefits of environmental education, such as fostering environmental awareness, promoting positive attitudes and behaviors towards the environment, and providing students with the knowledge and skills necessary to become responsible and engaged environmental citizens. The review also identified the benefits of community service learning, including promoting academic learning, personal and social development, and civic engagement. The study emphasized the need for further empirical research to explore the actual implementation and effectiveness of DepEd orders related to environmental education curriculum integration, investigate the role of community partnerships, and explore the impact of environmental education on student outcomes beyond just environmental knowledge and attitudes. Overall, the study suggests that environmental education and community service learning have the potential to enhance the curriculum and promote responsible and engaged environmental citizenship in the Philippines.